MULTIPLE COMBINATION PATTERNS OF OXA-TYPE CARBAPENEMHYDROLYZING AND METALLO-Β-LACTAMASES ENCODING GENES AMONG CLINICALLY ISOLATED ACINETOBACTER BAUMANNII. - NOPPADON JUMROON; PITAK SANTANIRAND (International Journal of Pharma and Bio Sciences, 2013)
Acinetobacter baumannii has recently become one of the most important nosocomial pathogens worldwide due to its resistance to nearly all available antibiotic including carbapenems. The most common mechanisms of carbapenem resistance are acquired OXA-type carbapenem-hydrolyzing class D β-lactamases (CHDLs) and metallo-β-lactamases (MBLs). The study determined the presence of CHDLs and MBLs encoding genes among A. baumannii recovered from Ramathibodi Hospital, Mahidol University, Thailand during May 2008 to March 2010. A total of 353 isolates of non-susceptible carbapenems A. baumannii were examined by Double-disk synergy test (DDST) of phenotypic MBLs detection and the simplex PCR assay of CHDLs and MBLs encoding genes were confirmed the positive phenotypic isolates. Twenty-six isolates of A. baumannii were positive DDST phenotypic method and the blaIMP-14a, blaOXA-23-like, blaOXA-24-like, and blaOXA-58-like were detected. It is first reported in Southeast Asia that demonstrated the combination of various carbapenem resistant genes among A. baumannii isolates.